2010
DOI: 10.1292/jvms.09-0398
|View full text |Cite
|
Sign up to set email alerts
|

Immune Recovery Effects of Immunopotentiator from Pantoea agglomerans 1 (IP-PA1) on Low Antibody Productions in Response to Salmonella Enteritidis Vaccine and Sheep Red Blood Cells in Dexamethasone-Treated Stressed Chicken Models

Abstract: ABSTRACT. Considering the usefulness of the immunopotentiator from Pantoea agglomerans 1 (IP-PA1), which is a purified lipopolysaccharide (LPS) derived from symbiotic gram-negative bacteria of food crops, in controlling immunosuppression in poultry husbandry, in this study, we examined its immune-recovery effects in dexamethasone-treated stressed chicken models. Three-week-old chickens daily administered 10 g/kg of dexamethasone for 35 days to induce stress showed more whole body weight loss; relative thymic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The SRBC antibody was determined by microagglutination (modified by Hebishima et al [30]). Serum samples taken on D7, D21, and D35 were inactivated by incubation at 56 • C for 30 min.…”
Section: Determination Of the Srbc Antibody (Against T-dependent Antimentioning
confidence: 99%
“…The SRBC antibody was determined by microagglutination (modified by Hebishima et al [30]). Serum samples taken on D7, D21, and D35 were inactivated by incubation at 56 • C for 30 min.…”
Section: Determination Of the Srbc Antibody (Against T-dependent Antimentioning
confidence: 99%
“…As the nutritional composition of diets in all groups was almost the same, the tendency to better egg quality seems to have been induced by Pantoea-6 ® and plant extracts. In this study, Pantoea-6 ® was made from extraction of fermented wheat flour with Pantoea agglomerans, which is gram-negative bacteria (Hebishima et al, 2010). Rajput et al (2013) reported that LPS is a structural component of the outer membrane of gram-negative bacteria.…”
Section: General Remarksmentioning
confidence: 99%
“…Hebishima et al (2010) reported that dexamethasone immunosuppression led to low antibody responses to a Salmonella Enteritidis vaccine in White Leghorn chickens suggesting that stressed chickens may have a higher risk of foodborne Fig. 3.…”
Section: Resultsmentioning
confidence: 99%